A History of Japanese Music - Harich-Schneider, Eta 1894-1986 (London Oxford University Press, 1973)
This study provides a chronological survey of two thousand years of musical activity in Japan. It begins with evidence discovered in prehistoric excavations, and includes discussions of surviving instruments, pictorial evidence, written records of successive periods, and the modern acceptance of Western music. Offering a comprensive view of the changes, developments, and consistencies in Japanese music-making, Harich-Schneider presents the social and political climate of each musical phenomena. An extensive portrayal of ancient and mysterious music, this history will interest musicologists and students of Japanese culture. (Publisher's description)
Bibliography: p. 598-617.
Accompanying sound recordings shelved in the Recorded Sound Section of the Motion Picture, Broadcasting, and Recorded Sound Division
Keywords: Music history; Japan